Design, cultura e tecnologia nos rótulos de cachaça da cidade de Curitiba nas décadas de 1950 e 1960 - Witikoski, Alan Ricardo (2009)
The present studies seek reflections on the relationship between design, culture and technology analyzed under the perspective of cachaça labels from the 50’s and 60’s, found at the cultural Foundation of the city of Curitiba, Paraná. the aim is to portray the various speeches on the same product of everyday life, from the idea of it being something regional, typical, in low-scale production and even handcrafted, until the building of a national identity, having it as a product for exportation produced in industrial scale. it is also aimed to rescue part of the history of brazilian graphic design. the semiotic analysis applied shows its importance as a tool for the development and understanding of the relationship between design, technology and culture. This provides the resources needed for the interpretation of plastic, iconic and linguistic aspects, evincing the interlacement among the technical processes, the traditions of engraving arising from lithography, the cultural values, the cultural and historical details and the construction of identities, revealing the richness and diversity of these labels.